CYTOKINE MODULATION IN CARDIAC SURGERY: CASE SERIES - DMITRIY L. Shukevich; ARTEM S. Radivilko; EGOR S. Sardin; ROMAN A. Kornelyuk; MIKHAIL S. Rubtsov; VERA G. Matveeva; EVGENIY V. Grigoriev (Фундаментальная и клиническая медицина)
Аim. Extracorporeal circulation, temporary aortic cross-clamping, cardioplegic arrest, perioperative heart failure, and comorbidities all are among the leading risk factors of a systemic inflammatory response syndrome (SIRS), which in some cases progresses to multiple organ failure (MOF). It has been recently suggested that sorption of inflammatory mediators using selective cytokine sorbents can prevent the development of MOF. We tested the efficacy of interleukin-6 (IL-6) sorption in pa-tients who underwent coronary artery bypass graft surgery requiring extracorporeal circulation with the subsequent development of sepsis (n = 9) and patients who was subjected to preventive adsorption during perfusion (n = 3). Materials and Methods. In addition to stan-dard clinical and biochemical parameters, we measured levels of serum IL-6 prior to the procedure, after the procedure and 24 hours after the sorption.Results. We noted a decrease in norepinephrine support and serum IL-6 as well as regression of MOF severity, particularly in patients with a preventive adsorption during the perfusion.Conclusions. IL-6 sorption is a promising method for correcting SIRS and MOF in patients who underwent coronary artery bypass graft sur-gery, particularly if applied in a preventive manner during the perfusion.